Language Use in Islamic Education: A Language Games Analysis from the Perspective of Ludwig Wittgenstein - Sriyanti; St. Nurhayati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Language plays a crucial role in shaping the learning process, particularly within Islamic educational settings where linguistic practices are intertwined with religious and pedagogical values. This study aims to analyze language use in Islamic education through the lens of language games as proposed by Ludwig Wittgenstein. Employing a qualitative descriptive approach, data were collected through classroom observations, interaction analysis, and documentation of teacher–student communication.The findings reveal that language use in Islamic classrooms is inherently contextual and governed by implicit rules that align with specific instructional and religious practices. Various forms of language use were identified, including instructional language, explanatory discourse, interrogative exchanges, and religious expressions. Each of these reflects distinct language games in which meaning is constructed through use rather than fixed definitions. Furthermore, the study highlights that the integration of religious expressions into classroom discourse enriches the complexity of language practices and reinforces shared understanding among participants. The application of Wittgenstein’s perspective demonstrates that meaning emerges dynamically within the social context of learning activities. This study contributes to the understanding of language as a socially embedded practice in Islamic education and offers insights for educators to develop more context-sensitive and effective communication strategies in the classroom.